Preparation for reaction time tasks in multiple sclerosis. Issue 3 (March 2016) - Cabib, C.; Llufriu, S.; Saiz, A.; Valls-Solé, J.
Abstract : Background: Sensorimotor integration can be assessed using simple reaction time tasks to somatosensory stimuli (ssRT). Tasks performed to stimuli applied to the contralateral hemibody would reveal interhemispheric transfer of information (IHT) across corpus callosum, while tasks performed when a startling-auditory stimulus (SAS) is presented together with the somatosensory cue would reveal the level of subcortical motor preparation. We studied both preparation and IHT in MS patients in whom callosal pathways and subcortical structures may be particularly involved. Methods: In 13 controls and 20 mildly disabled relapsing-remitting MS patients, we studied ssRT for voluntary wrist-extension to ipsilateral and contralateral low intensity electrical stimuli, applied to the index finger. Percentage delay (PD) of contralateral vs ipsilateral responses was calculated as a measure of IHT. StartReact trials were performed applying randomly a SAS in ssRT trials (20%). Percentage shortening (SAS-Short) with respect to ssRT was calculated as a measure of the effectiveness of preparation. Motor conduction time (MCT) was assessed by recording the motor-evoked potentials to TMS. Results: In controls, mean PD of contralateral responses was 105.7% longer than for ipsilateral responses. In StartReact trials, the mean SAS-Short was 29.7% for ipsilateral and 23.3% for contralateral responses. With respect to controls, patients had no differences in PD (105.4%) but showed significantly lower SAS-Short for ipsilateral (23.4%; p = 0.02) and contralateral trials (10.9%; p = 0.005). Contralateral SAS-Short was inversely correlated with MCT ( r = −0.294). Two patients had abnormally delayed orbiculari-oculi responses to SAS. Conclusions: Patients with MS have defective subcortical motor preparation that is worse when IHT sensorimotor integration is required.